Non-English Teacher Strategies in Implementing Merdeka Curriculum at Elementary School - Halim Budi Prasetyo; Nor Aida Aflahah; Tenny Murtiningsih (UMBanjarmasin, 2024)
This research aimed to analyse non-English teacher strategies in implementing Merdeka Curriculum at elementary school. The research was conducted for fourth-grade students at an elementary school in Banjarbaru. This research was a qualitative research method with case study approach, within classroom observation analysis and in-depth interview collecting data. The subjects of this research were a the fourth-grade teacher and the headmaster. The findings showed in the implementation of the strategies, the teacher did not make any differences both of Merdeka Curriculum and K13 Curriculum while teaching English. The findings also showed that the teacher used more than two strategies from the interview results. Beside of using discovery learning and cooperative learning as the teacher mentioned, most of the criteria that the teacher did in the classroom have several specific strategies such as expository learning, contextual teaching learning, and inquiry-based learning. Based on this result, both of Merdeka Curriculum and previous curriculum did not make any difference for the teacher to use the other strategies in the classroom. In fact, the teacher facing several obstacles while teaching Englsih in the classroom, such as the lack of english skill because did not have english background study, and the lack of understanding in the use of teaching strategies. The researcher suggested for being more aware of every strategy which use in the classroom and improving the english skill to make it easier while teaching English in the classroom.